1994
DOI: 10.1080/09553009414550261
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Response of Mouse Lymphoid and Myeloid Cell Lines. Part III. Different Signals Can Lead to Apoptosis and May Influence Sensitivity to Killing by DNA Double-strand Breakage

Abstract: We have examined the timing of gamma-irradiation-induced death in relation to cell cycle progression using a panel of mouse lymphoid or myeloid cell lines. Death was found to occur immediately after irradiation ('rapid interphase' death), or after arrest in G2 phase ('delayed interphase' death). In part II of this series of papers we demonstrated the occurrence of radiation-induced apoptosis in all these cell lines. This suggests that different signals can lead to apoptosis in these cell lines. DNA double-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…Such an arrest may take place at different points in the cell cycle. Exposure to radiation induced a more pronounced G 2 /M block, and in those cases apoptosis appeared to be manifest at the time of cells release from the G 2 /M block, during the subsequent G 1 phase [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Such an arrest may take place at different points in the cell cycle. Exposure to radiation induced a more pronounced G 2 /M block, and in those cases apoptosis appeared to be manifest at the time of cells release from the G 2 /M block, during the subsequent G 1 phase [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a good quantitative inverse relationship between micronucleus frequency and clonogenic survival (Wandl et al, 1989;Jamali and Trott, 1996;Mariya et al, 1997); however, there are also several reports in which such a correlation was not found (Bush and McMillan, 1993;Slavotinek et al, 1993;Villa et al, 1994). Some authors have reported an inverse correlation between apoptotic frequency and cell survival (Radford and Murphy, 1994;Olive and Durand, 1997;Guo et al, 1999), whereas others found no correlation (Yangihara et al, 1995;McKenna et al, 1996).…”
mentioning
confidence: 89%
“…In experimental animal tumors, apoptosis has been shown to occur following treatment with irradiation. 4,5) One such study reported that an acute apoptotic response after irradiation may be a feature of the radiosensitive tumor. 6) Spontaneous apoptosis is a mechanism of cell loss in untreated tumors, 3) so irradiation probably enhances the process of apoptosis that results in tumor cell death in irradiated patients.…”
mentioning
confidence: 99%